A Study on Software Components Governance Based on SOA Governance Elements - Albert, Benno; Santos, Rodrigo; Werner, Cláudia (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2012: Anais do VI Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2012)
Just as SOA (Service-Oriented Architecture) governance, software components management has many challenges related to promoting best practices on Software Reuse. SOA governance frameworks were elaborated in order to define and introduce SOA adoption and operation policies, as well as mechanisms to control its application. Considering the Component-based Software Engineering inhibitors, components governance is still a challenge in Software Reuse. This paper aims at analyzing whether essential elements included in SOA governance models can be applied to create a proposal of a framework for software components governance. The analysis was evaluated through an empirical study with experts from universities and companies and the results allowed to map the influence of the elements and its classification in three Software Engineering perspectives, i.e., people, process and technology.